Drive, instinct, reflex—Applications to treatment of anxiety, depressive and addictive disorders - Johnson, Brian; Brand, David; Zimmerman, Edward; Kirsch, Michael (Frontiers in Psychology, 2022)
The neuropsychoanalytic approach solves important aspects of how to use our understanding of the brain to treat patients. We describe the neurobiology underlying motivation for healthy behaviors and psychopathology. We have updated Freud’s original concepts of drive and instinct using neuropsychoanalysis in a way that conserves his insights while adding information that is of use in clinical treatment. Drive (Trieb) is a pressure to act on an internal stimulus. It has a motivational energic source, an aim, an object, and is terminated by the satisfaction of a surge of serotonin. An instinct (Instinkt) is an inherited pattern of behavior that varies little from species to species. Drives are created by internal/ventral brain factors. Instincts require input from the outside that arrive through dorsal brain structures. In our model unpleasure is the experience of unsatisfied drives while pleasure if fueled by a propitious human environment. Motivational concepts can be used guide clinical work. Sometimes what had previously described psychoanalytically as, “Internal conflict,” can be characterized neurobiologically as conflicts between different motivational systems. These motivational systems inform treatment of anxiety and depression, addiction in general and specific problems of opioid use disorder. Our description of motivation in addictive illness shows that the term, “reward system,” is incorrect, eliminating a source of stigmatizing addiction by suggesting that it is hedonistic. Understanding that motivational systems that have both psychological and brain correlates can be a basis for treating various disorders. Over many papers the authors have described the biology of drives, instincts, unpleasure and pleasure. We will start with a summary of our work, then show its clinical application.